ARSITEKTUR DVD (Digital Virtual Design) - Danny Santoso Mintorogo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2000)
Soon after the millennium year of 2000 and toward 21th century, the ways of architecture design will be a great change from traditional hand design and drawings to super computer digital virtual design models with tremendous of high-end architectural 3D software domains. Virtual Technology will be a plus to architectural design stage to obtain several